2021
DOI: 10.7717/peerj.11092
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the female athlete triad and injury rates in collegiate female athletes

Abstract: Background This study aimed to clarify the relationship between the triad risk assessment score and the sports injury rate in 116 female college athletes (average age, 19.8 ± 1.3 years) in seven sports at the national level of competition; 67 were teenagers, and 49 were in their 20s. Methods Those with menstrual deficiency for >3 months or <6 menses in 12 months were classified as amenorrheic athletes. Low energy availability was defined as adolescent athletes having a body weight <85% of ideal body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
1
2
0
1
Order By: Relevance
“…The results revealed that runners with FHA had more injury days and less annual running distance compared with the eumenorrheic runners, and only the eumenorrheic runners improved their performance over the year. 85 This study confirms the results from other research 86,87 that FHA is a potential predisposing factor for musculoskeletal overload injuries. Other reported predisposing factors are restricted EI, 88,89 DE behavior/EDs, 88 and low BMD.…”
Section: Injury and Illness Factorssupporting
confidence: 89%
“…The results revealed that runners with FHA had more injury days and less annual running distance compared with the eumenorrheic runners, and only the eumenorrheic runners improved their performance over the year. 85 This study confirms the results from other research 86,87 that FHA is a potential predisposing factor for musculoskeletal overload injuries. Other reported predisposing factors are restricted EI, 88,89 DE behavior/EDs, 88 and low BMD.…”
Section: Injury and Illness Factorssupporting
confidence: 89%
“…Thus, there is a critical need to educate dancers and other athletes regarding the Triad. Young female collegiate athletes engaged in long-distance sports compared to swimmers are at a higher risk of bone stress injuries and bursitis (risk categorization based on presence or absence of amenorrhea, low BMI and BMD) [36]. Among high school female runners, up to 25.8% report irregular menses [37], while in adult runners this number is as high as 62%.…”
Section: Hypothalamic-pituitary-gonadal Axismentioning
confidence: 99%
“…Além disso, a tríade da mulher atleta, caracterizada por distúrbios alimentares, ciclo menstrual irregular e baixa densidade mineral óssea, está associada com um maior número de lesões (EDAMA et al, 2021), além da associação das diferentes fases do ciclo menstrual com a frouxidão ligamentar e lesões de LCA (HERZBERG et al, 2017), que em suma apresentam um fator de risco elevado para atletas do sexo feminino.…”
Section: Ic (95%) Daunclassified